The impact of the classified voting system on corporate investment and equity value - Jin, Qinglu; Wu, Sirui (Contemporary Accounting Research, 2025)
Abstract Granting decision rights to minority shareholders protects them from expropriation by controlling shareholders, but it simultaneously fosters a mismatch between decision rights and decision‐relevant information. Using the setting of China's classified voting system (CVS), which requires minority shareholder approval for managerial proposals, this study investigates the effect of such a regulation on investment responsiveness to profitability and equity value attributable to growth options. Following the real‐options‐based valuation model, we document that the adoption of CVS diminishes both investment responsiveness and equity value. This reduction is attributed to heightened financial constraints following the CVS implementation. Further analyses show the negative impacts are more pronounced for firms experiencing greater information asymmetry, lower mutual fund holdings, and severe agency conflicts. Our evidence indicates that the efficacy of the regulation is contingent on the alignment between decision rights of minority shareholders and decision‐relevant information available to them. Our findings thus provide insights to the regulators regarding the advantages and disadvantages of allowing minority shareholders direct influence over corporate decision‐making.